2015
DOI: 10.1021/pr501141b
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Proteomics and Targeted Transcriptomics Analyses in Cardiac Endothelial Cells Unravel Mechanisms of Long-Term Radiation-Induced Vascular Dysfunction

Abstract: Epidemiological data from radiotherapy patients show the damaging effect of ionizing radiation on heart and vasculature. The endothelium is the main target of radiation damage and contributes essentially to the development of cardiac injury. However, the molecular mechanisms behind the radiation-induced endothelial dysfunction are not fully understood. In the present study, 10-week-old C57Bl/6 mice received local X-ray heart doses of 8 or 16 Gy and were sacrificed after 16 weeks; the controls were sham-irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 107 publications
6
74
0
Order By: Relevance
“…In the present study, proteins with ratio of heavy/light or medium/light greater than 1.3 fold or less than − 1.3 fold were considered to be significantly deregulated during senescence [22,23]. The biological significance of this fold change cut off is in good agreement with the previously published data [24,39].…”
Section: Proteomic Profiling Of Huvecssupporting
confidence: 87%
“…In the present study, proteins with ratio of heavy/light or medium/light greater than 1.3 fold or less than − 1.3 fold were considered to be significantly deregulated during senescence [22,23]. The biological significance of this fold change cut off is in good agreement with the previously published data [24,39].…”
Section: Proteomic Profiling Of Huvecssupporting
confidence: 87%
“…Endothelial cells proliferate rapidly in vitro and thus may not reflect the response of slowly proliferating endothelial cells of adult organs on ionizing irradiation. Proteomics analysis of cardiac endothelial cells isolated directly from mice that were locally irradiated to heart showed a significant inhibition of PI3K/Akt/eNOS pathway [8]. This study, using the isotope-coded protein label method, strongly suggested decreased NO availability and enhanced inflammation as the main causes of radiation-induced long-term cardiovascular dysfunction.…”
Section: Radiation-induced Changes In the Cardiac Endothelial Proteomementioning
confidence: 69%
“…This information adds to the knowledge about the effects of 5FU on the cardiovascular system. More generally, it highlights that anticancer treatment-induced senescence of endothelial cells, which so far has mainly been described and discussed for doxorubicin (Spallarossa et al, 2010;Hodjat et al, 2013;De Falco et al, 2016) and ionizing radiation (Azimzadeh et al, 2015;Park et al, 2016), may also be relevant for other oncological therapies. In the heart, 5FU-initiated senescence might at least in part contribute to coronary spasm and/or microvascular disease and might promote the formation and progression of coronary atherosclerotic lesions, as endothelial senescence has been implicated in atherogenesis (Yin and Pickering, 2016).…”
Section: Discussionmentioning
confidence: 98%